Cover Image. (21st December 2020) - Yin, Haoran; Luo, Mingkun; Luo, Wentao; Wang, Lanmei; Zhu, Wenbin; Fu, Jianjun; Dong, Zaijie
Abstract : The cover image is based on the Original Article miR-196a regulates the skin pigmentation of koi carp (Cyprinus carpio L.) by targeting transcription factor mitfa by Haoran Yin et al., https://doi.org/10.1111/are.14885 .